2009
DOI: 10.1097/pas.0b013e31819d17eb
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Index

Abstract: A concern of surgical oncologists has been to find a method to select patients for groin dissection in penile carcinomas considering the high morbidity of this procedure. A promising methodology, in the identification of early metastatic foci by the sentinel lymph node technique (initiated in Paraguay in the 1970s), was found, using a static anatomic approach, to be associated with a recurrence rate of 30%. Later, a dynamic method using radioactive tracers and peritumoral dye injection was introduced with an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 86 publications
(15 citation statements)
references
References 59 publications
1
13
1
Order By: Relevance
“…Previous studies have found that the metastatic rate of tumors invading corpus cavernosum is higher than those tumors limited to corpus spongiosum (Chaux et al. 2009). Furthermore, splitting the pT2 stage in two categories depending on invasion of corpus spongiosum vs. corpus cavernosum has proven useful in increasing the accuracy of the TNM system for predicting outcome (Leijte et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have found that the metastatic rate of tumors invading corpus cavernosum is higher than those tumors limited to corpus spongiosum (Chaux et al. 2009). Furthermore, splitting the pT2 stage in two categories depending on invasion of corpus spongiosum vs. corpus cavernosum has proven useful in increasing the accuracy of the TNM system for predicting outcome (Leijte et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…An anatomical level-based approach, combined or not with measurement of tumor thickness, has been evaluated and found useful (Chaux et al. 2009; Velazquez et al. 2008).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations